Pros and Cons of Round Window Vibroplasty in Open Cavities: Audiological, Surgical, and Quality of Life Outcomes. Issue 6 (July 2015) - Lassaletta, Luis; Calvino, Miryam; Sánchez-Cuadrado, Isabel; Pérez-Mora, Rosa M.; Muñoz, Elena; Gavilán, Javier
Abstract : Objective: To evaluate the audiological, surgical, quality of life, and quality of sound outcomes in adults with open cavities implanted with the Vibrant Soundbridge (VSB) implant using round window (RW) vibroplasty approach. Study Design: Retrospective study. Setting: Otolaryngology department, tertiary referral hospital. Subjects and Methods: Twelve adult patients with conductive or mixed hearing loss, all with previous middle ear surgery, underwent RW vibroplasty in an open cavity. Compound action potential thresholds were assessed during surgery. Surgical complications were recorded. Subjective benefit was evaluated using the Nijmegen Cochlear Implant Questionnaire (NCIQ), Glasgow Benefit Inventory (GBI), and Hearing Implant Sound Quality Index (HISQUI29 ) tests. Results: Mean follow-up was 42 months (range 12–76). There was no significant change in bone conduction thresholds after surgery. Mean functional gain was 34.3 dB and speech discrimination score at 65 dB significantly improved from 14 to 83%. Extrusion of the wire link was the main surgical complication in four patients. All NCIQ domains improved after surgery. All patients had a positive overall GBI score (mean 35.0). Mean HISQUI29 score was 152.8, on average the quality of sound being defined as "very good." Conclusion: VSB is an effective method of hearing restoration for adults with open cavities suffering from conductive or mixed hearing loss. Intraoperative electrocochleography may be considered of significant help to check the coupling to the inner ear. The high rate of extrusion suggests that middle ear obliteration may be considered in these patients.